Identifikasi Bauran Pemasaran Pada Usaha Salad Buah "Bellfood" Di Desa Wasian Kecamatan Kakas Barat - Kalengkongan, Gracia Natasya; Benu, Noortje Marsellanie; Tangkere, Ellen Grace (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to identify the marketing mix in the Fruit Salad Business “Bellfood” in Wasian Village, West Kakas District, Minahasa Regency. The research time was conducted for 3 months, namely from September to November 2023 from preparation to preparation of research reports. This research was conducted at Bellfood Fruit Salad which is located at Wasian Village, West Kakas District, Minahasa Regency. The data used in this research are primary data and secondary data. Primary data is obtained from direct observations and interviews with consumers, while secondary data is obtained from literature searches through books, literature, mass media, and writings related to the research topic. The results of the research on the Marketing Mix of the Bellfood Fruit Salad business in Wasian Village, West Kakas District, Minahasa Regency, that the Bellfood Fruit Salad business marketing mix of 4 variables and 11 indicators as benchmarks in this study product, price, promotion, place, which reached a total achievement of 989 and was classified as good.